Development of a triplex real-time quantitative PCR for detection and differentiation of genotypes I and II African swine fever virus - Qian, Xinxiu; Hu, Liping; Shi, Kaichuang; Wei, Haina; Shi, Yuwen; Hu, Xin; Zhou, Qingan; Feng, Shuping; Long, Feng; Mo, Shenglan; Li, Zongqiang (Frontiers in Veterinary Science, 2023)
African swine fever virus (ASFV) was first identified in 1921 and is extensively prevalent around the world nowadays, which has a significant negative impact on the swine industry. In China, genotype II ASFV was first discovered in 2018, and has spread quickly to different provinces in a very short time; genotype I ASFV was first found in 2020, and has been reported in several provinces since then. To establish an accurate method for detection and differentiation of genotypes I and II ASFV, three primers and probes were designed targeting the ASFV B646L gene for different genotypes, the F1055L gene for genotype I, and the E183L gene for genotype II, and a triplex real-time quantitative PCR (qPCR) for differential detection of genotypes I and II ASFV was developed after optimizing the reaction conditions. The assay showed high sensitivity, and the limits of detection (LOD) of the B646L, F1055L, and E183L genes were 399.647 copies/reaction, 374.409 copies/reaction, and 355.803 copies/reaction, respectively; the coefficients of variation (CVs) of the intra-assay and the inter-assay were 0.22%-1.88% and 0.16%-1.68 %, respectively, showing that this method had good repeatability; the assay could detect only ASFV, without cross-reaction with other swine viruses including PRRSV, PEDV, PDCoV, CSFV, PRV, PCV1, and PCV2, showing excellent specificity of this method. A total of 3,519 clinical samples from Guangxi province, southern China, were tested by the developed assay, and 8.16% (287/3,519) samples were found to be positive for ASFV, of which 0.17% (6/3,519) samples were positive for genotype I, 7.19% (253/3,519) samples for genotype II, and 0.80% (28/3,519) samples for genotypes I and II. At the same time, these clinical samples were also tested by a previously reported multiplex qPCR, and the agreement between these two methods was more than 99.94%. In summary, the developed triplex qPCR provided a fast, specific and accurate method for detection and differentiation of genotypes I and II ASFV.